2020
DOI: 10.3390/cancers12061475
|View full text |Cite
|
Sign up to set email alerts
|

Non-Small-Cell Lung Cancer Signaling Pathways, Metabolism, and PD-1/PD-L1 Antibodies

Abstract: Treatment of advanced (metastatic) non-small-cell lung cancer (NSCLC) is currently mainly based on immunotherapy with antibodies against PD-1 or PD-L1, alone, or in combination with chemotherapy. In locally advanced NSCLC and in early resected stages, immunotherapy is also employed. Tumor PD-L1 expression by immunohistochemistry is considered the standard practice. Response rate is low, with median progression free survival very short in the vast majority of studies reported. Herein, numerous biological facets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 207 publications
(273 reference statements)
0
65
0
1
Order By: Relevance
“…Response rate is low, with median progression free survival, that is generally short-lived (12). It is possible, as above described, that if tumor PD-1 is in equilibrium with tumor PD-L1, the disruption of intratumoral PD1-PD-L1 induced by monoclonal antibodies that block PD-1 (nivolumab or pembrolizumab) or PD-L1 (atezolizumab, durvalumab and avelumab) can provoke tumor hyper-progression which has been reported in several studies (13) (Figure 1). The figure summarizes the previous reports on the conflicting role that PD-1 or PD-L1 monoclonal antibodies could have in causing tumor progression.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Response rate is low, with median progression free survival, that is generally short-lived (12). It is possible, as above described, that if tumor PD-1 is in equilibrium with tumor PD-L1, the disruption of intratumoral PD1-PD-L1 induced by monoclonal antibodies that block PD-1 (nivolumab or pembrolizumab) or PD-L1 (atezolizumab, durvalumab and avelumab) can provoke tumor hyper-progression which has been reported in several studies (13) (Figure 1). The figure summarizes the previous reports on the conflicting role that PD-1 or PD-L1 monoclonal antibodies could have in causing tumor progression.…”
Section: Discussionmentioning
confidence: 90%
“…In our opinion, in addition to assessing patients for PD-L1 expression in the tumor, the expression of PD-1 in the tumor could serve as a potential biomarker to define efficacy or tumor progression following immunotherapy with either anti-PD-1 o anti-PD-L1 monoclonal antibodies (13).…”
Section: Discussionmentioning
confidence: 99%
“…Herein, immune checkpoints were selected to be evaluated between these two pIRS groups. This part of results revealed that PDCD1 [24], ICAM1 [25], and GZMA [26], which were associated with proactivity of cytotoxic T lymphocytes and cancer immunity, were predictive of prolonged prognosis in low pIRS group, and VEGFA, as the leading molecule of tumor-induced angiogenesis for tumor invasion [27], exhibited an increased expression in breast cancer patients with limited survival of patients from high pIRS group.…”
Section: Discussionmentioning
confidence: 94%
“…The estrogen pathway and its components may possess carcinogenic properties in LC and act as potential targets [ 128 131 ]. The programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) pathway is involved in the regulation of tumor-related immune processes, and it is a key target of cancer immunotherapy, which attempts to suppress immune escape and enhance antitumor immunity for the durable regression of malignant tumors of LC [ 132 134 ]. The dysfunction of genes and proteins comprising the p53 pathway, one of the common carcinogenic causes, is associated with various cancerous behaviors of LC cells, such as uncontrolled proliferation, survival, and cell cycle progression [ 61 , 63 , 135 – 143 ].…”
Section: Discussionmentioning
confidence: 99%